Remineralizing efficiency of two dentifrices clinically evaluated by DIAGNOdent quantitative light-induced fluorescence, in vivo study - Carla Tatiana Bravo Iñaguazo; Mayra Alejandra Núñez Aldaz; David Flores; Ana Del Carmen Armas Vega (Asociación Latinoamericana de Odontopediatría, 2019)
Objective: To compare the efficacy of two dentifrices with different composition, one containing arginine, calcium and fluoride and other fluoride thoothpaste, which were used for daily brushing of carious lesions, evaluated by DIAGNOdent system. Materials and Methods: Two groups of 20 students, aged 12 to 14 years, with non cavitated carious lesions were evaluated using DIAGNOdent light. They were instructed to brush twice a day with one of the tested dentifrices, one containing arginine 1.5% insoluble calcium and 1450 ppm fluoride, and the other containing 1450 ppm fluoride, for a period of 90 days. DIAGNOdent assessment of tooth surfaces was performed every 30 days, and data were statistically evaluated using the Mann Whitney test. Results: The values obtained in the three measurements of each of the surfaces, at 30, 60 and 90 days, were compared between groups, determining that there were significant differences between the two dentifrices (p=0.008) with better performance in terms of remineralization for the Arginine-Calcium-Fluoride based dentifrice. Conclusion: The remineralizing action of the two toothpastes allowed to revert the destruction of the enamel tissue affected by non cavitated carious lesions; however, the performance of the toothpaste containing arginine-fluoride and calcium proved better during the 90 days of evaluation.